Micro-Zonation Mapping of Landslide Potential Using Statistical Weighting Method of Analytical Hierarchy Process (AHP) in South Bengkulu–Lahat Road for Disaster Mitigation - Arif Ismul Hadi; Budi Harlianto; Nurul Hudayat; M. Farid; Frinsyah Virgo; Darmawan Ikhlas Fadli; Fadillah Humairah (Postgraduate, University of Mataram, 2025)
The research objective was to identify areas with high, medium, and low potential for landslides by micro-zonation on the South Bengkulu–Lahat road, map areas with potential for landslides based on the parameters that contribute to causing landslides using the AHP method, and determine the parameters for landslides, the dominant parameter affecting the occurrence of landslides in the study area. To achieve the research objectives, all parameters that cause landslides obtained at measurement points are then overlaid using the AHP statistical weighting method. The results showed that the area along the South Bengkulu–Lahat road had been identified microzoning high, medium, and low landslide potentials based on statistical weighting from parameters were obtained at the measurement points. For areas with high landslide potential, caution should be exercised, especially during the rainy season with high intensity and long duration.